Education and gendered citizenship in Pakistan - Naseem, M. Ayaz (Muhammad Ayaz), 1963- (Palgrave Macmillan's postcolonial studies in education., 2010)
Education and Gendered Citizenship in Pakistan challenges the uncritical use of the long held dictum of the development discourse that education empowers women. Situated in the post-structuralist feminist position, it argues that in its current state the educational discourse in Pakistan actually disempowers women. Through a systematic examination of the educational discourse in Pakistan, Naseem argues that the educational discourse (through curricula, textbooks, and pedagogical practices) constitutes gendered identities and positions them in a way that exacerbates and intensifies inequalities between men and women on one hand and between the dominant and minority groups on the other. Gendered constitution and positioning of subjects also regulates the relationship between the subjects and the state in a way that women and minorities are excluded from the development and citizenship realms. Finally, Naseem uncovers the mechanisms through which the educational discourse in Pakistan constitutes a militant nationalism and militaristic nationalistic subjects.